2021
DOI: 10.1016/j.socec.2020.101613
|View full text |Cite
|
Sign up to set email alerts
|

Social preferences across different populations: Meta-analyses on the ultimatum game and dictator game

Abstract: We perform meta-regressions on a single database containing 96 observations of simple ultimatum games and 144 observations of simple dictator games to disentangle the fairness hypothesis based on the degree of economic development of a country. According to the fairness hypothesis, offers in the two games should not differ if they were motivated by a subject's fairness concerns. Using the difference across countries between offers in ultimatum and dictator games, we address the effect of being exposed to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 119 publications
0
11
2
1
Order By: Relevance
“…60% of participants gave the same amount in both games. Of the remaining 40%, all but one participant (37.14%) gave the other person more money in the Ultimatum Game than in the Dictator Game, which is to be expected 26 .…”
Section: Dictator Game and Ultimatum Game Make Offersmentioning
confidence: 75%
See 1 more Smart Citation
“…60% of participants gave the same amount in both games. Of the remaining 40%, all but one participant (37.14%) gave the other person more money in the Ultimatum Game than in the Dictator Game, which is to be expected 26 .…”
Section: Dictator Game and Ultimatum Game Make Offersmentioning
confidence: 75%
“…Compared to previous studies, our participants were surprisingly generous. A recent meta-analysis 26 of studies using Dictator Games and Ultimatum Games found that people offer the other person on average 25% of the money in the Dictator Game and 42% in the Ultimatum Game. In our study, participants offered the other person on average 41% of the money in the Dictator Game and 50% in the Ultimatum Game, thus offering the other person much more than other studies typically find.…”
Section: Discussionmentioning
confidence: 99%
“…These results are perhaps best understood when compared with existing findings on how non-elites play the ultimatum game. Meta-analyses of ultimatum game studies find that proposals in industrialized societies amount to about 40%–43% of the shared pie, on average, and rarely exceed 50% (Cochard et al 2021; Oosterbeek, Sloof, and Van De Kuilen 2004; Tisserand 2014, see also Eckel and Grossman 2001). The offers made by politicians in our sample are substantially higher, averaging 54% of the endowment, or 11–14 percentage points (pp) higher than those population figures.…”
Section: Resultsmentioning
confidence: 99%
“…Además, Brañas (2006) realiza una investigación del efecto de la pobreza en la aplicación del juego del dictador forzando la aversión a la inequidad, manifestándoles a los participantes con el rol del dictador que los beneficiarios provenían de países con recursos escasos. De manera análoga, Bolton et al (1998) presentan un proceso de decisión hipotético, donde le otorgan al rol del dictador reglas sociales y personales que limitan de manera eficaz el comportamiento egoísta; y Cochard et al (2021) donde estudian las diferencias en las ofertas en los juegos del ultimátum y dictador en varios países con una hipótesis de equidad, encontrando que las personas de países más desarrollados tienden a dar menos en las ofertas del juego del dictador.…”
Section: Marco Teóricounclassified